Pendekatan Supply Chain Management Untuk Meningkatkan Daya Saing Pada Bisnis Bunga Segar - Cahyani, Rusnandari Retno (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2014)
In global business, each company requires to provide cheap products, good quality and services, and  appropriate customer orders. Supply chain  management should be adopted by the company  in order to  survive  and  win the market competition. This study aims to investigate the implementation of supply chain  management  in a fresh flower business, to observe the benefit of adopting the  supply  chain management  which  is assessed  from  goods suppliers, and to evaluate  the  distribution  implementation  to  the  customer. Supply chain management approach is conducted by involving all the interactions among suppliers, manufacturers, distributors,  and customers. The  chain  covers not only  transportation, scheduling information, cash and credit transfer, but also the transfer of ideas, designs, and materials. This research is a qualitative descriptive study. In conclusion, it is shown that the supply chain management approach potentially improves the competitiveness of the fresh flower business.Keyword: Customer, Distribution, and Supply Chain Management